Blood monoamines as potential biomarkers for conditioned pain modulation efficacy: An exploratory study in paediatrics. (14th September 2018) - Ferland, Catherine E.; Teles, Alisson R.; Ingelmo, Pablo; Saran, Neil; Marchand, Serge; Ouellet, Jean A.
Abstract: Background: Monoaminergic pathways are involved in the process of pain inhibition and facilitation. The objective of this study was to investigate the role of blood monoamines as biomarkers of conditioned pain modulation (CPM) efficacy. Methods: One hundred and five paediatric patients with chronic back pain were enrolled in this observational study. The protocol involved dosage of plasma monoamines (dopamine, DOPA; serotonin, 5‐HT; epinephrine, Epi; norepinephrine, NE; metanephrine, ME; and normetanephrine, NME) and clinical assessment (CPM, functional disability, pain, sleep quality, anxiety and depression). Results: 5‐HT and DOPA were positively correlated among each other and were both negatively correlated with Epi, ME, NE and NME. CPM presented a positive correlation with DOPA and 5‐HT. On the other hand, Epi, ME, NE and NME correlated negatively with CPM. Different correlation coefficients were observed between genders, with stronger coefficients being observed in the male subpopulation. Stepwise regression controlling for age and gender indicated that ME (B = −0.987, SE (B) = 0.299, p = 0.002) was the only significant predictor for CPM efficacy. Higher blood ME was associated with poorer CPM efficacy. ME explained 53% of variation of CPM in males ( R 2 = 0.536, p < 0.0001) and 7% in females ( R 2 = 0.074, p = 0.014). In males, blood ME >15 pg/ml predicted inefficient CPM with 88.9% sensitivity and 83.3% specificity. Conclusions: Our findings suggest that ME can be a potential biomarker for CPM efficacy in paediatrics. Future studies are needed to assess the efficacy of tailored treatments for pain according to blood ME. Significance: We were able to demonstrate an association between CPM and circulating monoamines. In the clinical setting, sampling ME could provide the clinician an idea of the individual's pain modulation potential. This may be particularly important for children with cognitive impairment, for whose CPM paradigm cannot be used.